1999
DOI: 10.1007/s100510050783
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering by transverse waves in supercooled liquids and application to metatoluidine

Abstract: We discuss the hydrodynamic equations which describe the shear dynamics of a liquid composed of anisotropic molecules, both in its normal and its supercooled phases. We use these equations to analyze 90 • depolarized light scattering experiments performed in the supercooled phase of a glass forming liquid, metatoluidine, and show that the information extracted from this analysis is consistent with independent shear viscosity measurements performed on that liquid in the same temperature range. PACS. 66.20.+d Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…One of a very powerful tool in studies of glasses is Brillouin spectroscopy since it has been shown to give valuable information on the dynamical properties of glass-forming materials in the gigahertz region. [1][2][3][4][5][6][7][8] The relaxational processes have been extensively studied for glass formers without directional bonds, which show a similar high increase of viscosity upon supercooling and are called fragile systems. 3,6,7 The dynamics of these fragile systems is relatively well understood on the basis of mode coupling theory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of a very powerful tool in studies of glasses is Brillouin spectroscopy since it has been shown to give valuable information on the dynamical properties of glass-forming materials in the gigahertz region. [1][2][3][4][5][6][7][8] The relaxational processes have been extensively studied for glass formers without directional bonds, which show a similar high increase of viscosity upon supercooling and are called fragile systems. 3,6,7 The dynamics of these fragile systems is relatively well understood on the basis of mode coupling theory.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The relaxational processes have been extensively studied for glass formers without directional bonds, which show a similar high increase of viscosity upon supercooling and are called fragile systems. 3,6,7 The dynamics of these fragile systems is relatively well understood on the basis of mode coupling theory. 6,9 On the other hand, in the presence of directional bonds the temperature variation of viscosity is weaker, and the dynamics of these so-called strong and intermediate glass formers is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic transducer [10,11], Impulsive Stimulated Scattering (ISS) [12][13][14] and highfrequency forced Brillouin Scattering [15] techniques can continuously cover the longitudinal spectrum up to the * kanelson@mit.edu mid-GHz regime. However, broadband shear wave generation is more accessible experimentally at lower frequencies and exhibits a gap in the range from the ∼ 10 MHz limit of transducer methods [10,11] to the low GHz frequencies probed by depolarized (VH) Brillouin Scattering [16][17][18][19][20][21]. The vast majority of depolarized Brillouin Scattering studies are conducted in a single scattering geometry, permitting observation of only one acoustic wavevector.…”
Section: Introductionmentioning
confidence: 99%
“…The observed differentiation can be attributed to non-random spatial orientation correlations due to rotation-translation coupling proposed for small molecules. [52][53][54][55][56] For semi-flexible polymers, however, the effect is strong and the dynamics are slow that renders the finding unique. A further advantage is the observation of the effect at equilibrium without macroscopic flow.…”
Section: Helical Chainsmentioning
confidence: 99%